Pengembangan Media Pembelajaran berbasis WEB pada Mata Pelajaran Komputer dan Jaringan Dasar Kelas X SMK Negeri 5 Malang - Tites Agung Prabowo; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
At a time like this with the COVID-19 pandemic, the government urges all educational institutions to organize distance learning activities. At SMK Negeri 5 Malang, teachers are required to carry out distance learning which is no less interesting than face-to-face learning. However, teachers do not innovate much in providing reference for learning materials during distance learning so that teachers cannot create learning media that attract the attention of students. One solution that can be applied to deal with these problems is by developing student learning aids in the form of website-based learning media in order to improve learning outcomes and affect student learning interactions and motivation in Computer and Basic Networking subjects. This research method is Research and Development (R&D) with ADDIE development method (Assessment/Analysis, Design, Development, Implementation, Evaluation). Learning media is made with the help of the Wordpress application. The data collection instruments were observation, interviews and questionnaires. The feasibility of this learning media was assessed by a team of media experts, and students. The analysis of the data from the feasibility results was carried out using the help of a Likert scale. The results showed that: (1) web-based learning media had been developed with the address https://komjardas2020.wordpress.com/ . (2) Web-based learning media on Application Software Installation Problems material is feasible to be used as a learning medium, judging from the results of the assessment by students as users of website-based learning media in obtaining a percentage of 88.46%.